Gambogic acid-iron nanozymes as effective carriers for enhanced chemotherapy by inducing excessive autophagy and oxidative stress - Yang Qiao; Menghui Liu; Yiqun Zhang; Fan Ni; Liangchen Yu; Zhao Chen; Xingliang Dai; Xianwen Wang (Journal of Nanobiotechnology)
Abstract The complex dual role of autophagy provides new insights for enhancing tumor treatment efficacy. However, effectively regulating this process is key to enhancing therapeutic efficacy. To address this challenge, this study designed a gambogic acid-iron nanozyme (GAFe) as a novel carrier to enhance the effectiveness of chemotherapy drugs such as doxorubicin (DOX) by inducing excessive autophagy and oxidative stress. The synthesized nanoparticle (GAFe@DOX) is capable of slowly releasing its active components over a prolonged period within tumor tissues. Gambogic acid can induce excessive autophagy, while the multi-enzyme activity of GAFe and the activation of ferroptosis amplify and sustain excessive autophagy, thereby enhancing the chemotherapy effect of DOX. Meanwhile, ferroptosis activated via the GPX4 pathway by GAFe can synergize with excessive autophagy, amplifying oxidative stress and consequently enhancing the overall therapeutic efficacy. Characterization experiments confirmed the successful synthesis of GAFe@DOX and probe assays demonstrated its superior multi-enzyme activity. In vitro cell studies showed that GAFe@DOX effectively kills tumor cells, while in vivo animal experiments revealed its excellent biocompatibility and significant tumor growth inhibition. This study demonstrates a promising strategy to improve tumor therapeutic efficacy by modulating excessive autophagy and oxidative stress. This provides a novel and effective approach to improve the treatment of refractory tumors such as glioblastoma. Graphical abstract